Legitimizing private legal systems through CSR communication: a Walmart case study. (5th August 2019) - Harrison, Virginia
Abstract : Purpose: The purpose of this paper is to understand the role of corporate social responsibility (CSR) communications in business by merging previously unconnected lines of thought in communications and law. Using Walmart as an example, the study shows that CSR communication can legitimize a corporation's autonomous legal system of regulation and governance over its business practices. Design/methodology/approach: A qualitative case study of all online corporate communications webpages from Walmart was examined. Discourse and qualitative analyses were used to show how language and online communications practices created actional legitimacy for Walmart's CSR practices. Findings: Using the UN's Guiding Principles for Business as a framework for analysis, the study demonstrated how CSR communications helps Walmart to establish its own system of CSR norms, structures and remediation processes for its business outside of the state. These communications also sought to legitimize these actions among stakeholders. Research limitations/implications: This case study looks at one corporation (Walmart) to illustrate a new connection between CSR communication and legitimacy. Future research in communications can extend this line of inquiry by examining how communications can reinforce autonomous legal systems and public perceptions. Originality/value: Backer's (2007) autonomous legal system and the concept of actional legitimacy in communications have not yet been studied systematically. This case study demonstrates how CSR communications can legitimize a multinational corporation's business practices, which, in turn, raises ethical considerations for the ways this communication serves the greater society.